Study on the Potential for Development of Ra'ra Mangrove Ecotourism in Balang Baru Village, Tarowang District, Jeneponto Regency, South Sulawesi - Danial, Danial; Syahrul, Syahrul; Hamsiah, Hamsiah; Tang, Beddu; M. Anwar, Alifah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to determine the potential of mangrove ecotourism and to determine the level of suitability of mangrove ecotourism. It is hoped that it can provide information and references for the management of ecosystem areas and contribute to analyzing the potential level of mangrove ecotourism development. This research was carried out in August-October 2021, then data analysis and report preparation was carried out until March 2022. Ecotourism suitability analysis is a study to assess the suitability of an activity carried out in an area according to resource potential and its designation by considering various parameters. The mangrove forest environment is expected to provide lessons for visitors and the surrounding community. The ecotourism potential of Ra'ra mangroves has a natural tourist attraction with an area of approximately 15.29 ha which consists of various kinds of activities that can be carried out by visitors, including enjoying the mangrove forest ecosystem with various kinds of flora and fauna, a 200-meter mangrove track. In addition, there is an area of 7.79 ha which can be used as a mangrove conservation location. the total value of IKW is 23. The number of Ecowisa Ra'ra Tourism Conformity Index is 58.97 with the Conformity Category which is in accordance with the Standards of the Tourism Conformity Index.